Gambaran Status Gizi terhadap Riwayat Sindrom Metabolik pada Lansia di UPTD Griya Werdha Surabaya - Anisah Nur Fitria; Farapti Farapti (Universitas Airlangga, 2023)
Background: Metabolic syndrome (SM) is a syndrome consisting of a number of symptoms including increased waist circumference, increased blood triglyceride levels, decreased levels of high-density lipoprotein (HDL)-blood cholesterol, high blood pressure, and glucose intolerance. The criteria for metabolic syndrome based on the National Cholesterol Education Program (NCEP) modified for the Asian region state that a person is diagnosed with SM if he has 3 of the 5 symptoms. The importance of managing the nutrition of the elderly in a group is expected to improve the quality of life of the elderly, including the elderly group in social institutions. Research data from the previous year, 80% of the elderly at UPTD Griya Werdha Surabaya experienced malnutrition and weight loss, and had insufficient intake. In addition, 64.8% had hypertension, 33% had gout, 27.8% had hypercholesterolemia, and 13% had diabetes mellitus, and more than 20% had multiple diseases. Objectives: to describe of the nutritional status of the elderly on a history of metabolic syndrome in the elderly at UPTD Griya Werdha Surabaya and to analyze the relationship between nutritional status and a history of metabolic syndrome in the elderly at UPTD Griya Werdha Surabaya. Methods: This research is an observational cross-sectional study to describe the nutritional status of a history of metabolic syndrome in the elderly at UPTD Griya Werdha Surabaya. The research variables were nutritional status and history of metabolic syndrome. The instruments used were a respondent characteristic questionnaire form containing name, gender, age, and education and the MNA (Mini Nutritional Assessment) form. The total sample is 60 elderly people selected using simple random sampling. Results: The results showed that 26 elderly (43.3%) had a history of metabolic syndrome, that is 8 male elderly and 18 female elderly. According to the MNA, there are 36 elderly who are at risk of malnutrition and 2 suffer from malnutrition. Nutritional status based on BMI (Body Mass Index), that is 9 elderly people experiencing malnutrition, 31 normal nutrition, and 20 overweight. Malnutrition according to MNA showed no association (p=0.139) with a history of metabolic syndrome, while malnutrition based on BMI had an association (p<0.001) with a history of metabolic syndrome. Conclusions: The conclusion obtained in this study is that overweight status (BMI³25) has a relationship with a history of metabolic syndrome.